The Relationship between Personality Traits, Parental Involvement in their Children\'s Education, and Students’ Academic Motivation - S.M. Pourseyed, Ph.D.; M. Fouladchang, Ph.D.; S.R. Pourseyed, Ph.D. (خانواده و پژوهش, 2019)
The present research sought to examine the relationship between personality traits, parental involvement in their children's education, and students’ academic motivation. The statistical population of the study comprised all high school students in Abarkooh in academic year 2014-2015. A sample of 250 students (149 girls and 101 boys) was drawn using multi-stage cluster sampling method. The instruments included Academic Motivation Scale (AMS, Vallerand et al., 1992(, Neo-Five Factor Personality Inventory )NEO-FFI(, and Parental Involvement  Scale (Sanaee, 1996(. The results demonstrated that extraversion, openness, agreeableness, conscientiousness and parental involvement had significant, direct relationships with intrinsic motivation; however, openness, conscientiousness, and parental involvement could strongly predict intrinsic motivation. Furthermore, extraversion, agreeableness, conscientiousness and parental involvement had significant, direct relationships with extrinsic motivation; however, only conscientiousness and parental involvement could strongly predict extrinsic motivation. Moreover, openness, agreeableness, and conscientiousness had significant, negative relationships with amotivation; however, only openness and conscientiousness could strongly predict amotivation. It is worth mentioning that conscientiousness could account for the variation in intrinsic motivation, extrinsic motivation, and amotivation the most.